Lateral Torsional Buckling of Wooden Beams with Mid-span Lateral Bracing offset from Section Mid-height - Hu, Ye; Mohareb, Magdi; Doudak, Ghasan (Université d'Ottawa | University of Ottawa, 2017)
An energy-based solution is developed for the lateral torsional buckling analysis of wooden beams with a mid-span lateral brace subjected to uniformly distributed loads or mid-span point load. The predicted critical moments and mode shapes are shown to agree with results based on three- dimensional finite element analysis. The study indicates that such beams are prone to two buckling patterns: a symmetric mode and an anti-symmetric mode. Whether the symmetric or the anti-symmetric mode governs the critical moment capacity is shown to depend on the bracing height. A technique is then developed to determine the threshold bracing height required to maximize the critical moment. A parametric study is then conducted to investigate the effect of lateral bracing and load height effects on the critical moments. Simple design equations are developed to predict critical moments for a practical range of cases. The limitations of the simplified procedure are discussed. For cases outside the scope of the simplified procedure, designers are recommended to adopt the more detailed energy-based solution. Design examples are provided to illustrate the merits and applicability of the proposed procedure in practical situations.
Keywords: Lateral torsional buckling; lateral bracing; load height; bracing height; simplified design equations